2015
DOI: 10.1007/978-3-319-16077-1_8
|View full text |Cite
|
Sign up to set email alerts
|

Everything but the ACD, Functional Conservation of the Non-conserved Terminal Regions in sHSPs

Abstract: At the primary level small heat shock proteins are commonly described as a conserved α-crystallin domain fl anked by regions that have disparate sequence content. While this holds true when analysing simple pairwise alignments, it belittles the importance of these N-terminal and C-terminal extensions. Careful examination of their sequences, combined with an improved understanding of the structure and activity of these proteins, yields an alternative view where the N-and C-terminal arms play an important role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 130 publications
(199 reference statements)
0
11
0
Order By: Relevance
“…The various sHSP truncations ultimately point to the NTD, a region predicted to be unstructured [20,33], as being essential for driving the specific heterodimerization of HSPB1…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The various sHSP truncations ultimately point to the NTD, a region predicted to be unstructured [20,33], as being essential for driving the specific heterodimerization of HSPB1…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the NTD in defining the heterodimer interface, located at the ACD, is quite remarkable. Truncation or post-translational modification of this region often leads to smaller assemblies typically pointing to its recognized role in higher-order oligomerization rather than dimer formation [33]. It was reported that phosphorylation of the N-terminal serine residues of HSPB5 led to a loss of the dimeric substructure within the larger oligomer species, but this was hypothesized to be the result of a reduced interaction of individual subunits within the whole assembly [37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations